Effectiveness of remdesivir in patients with COVID-19 under mechanical ventilation in an Italian ICU. (23rd August 2020) - Pasquini, Zeno; Montalti, Roberto; Temperoni, Chiara; Canovari, Benedetta; Mancini, Mauro; Tempesta, Michele; Pimpini, Daniela; Zallocco, Nicoletta; Barchiesi, Francesco
Abstract: Background: Remdesivir is a prodrug with in vitro activity against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Its clinical efficacy in patients with COVID-19 under mechanical ventilation remains to be evaluated. Methods: This study includes patients under mechanical ventilation with confirmed SARS-CoV-2 infection admitted to the ICU of Pesaro hospital between 29 February and 20 March 2020. During this period, remdesivir was provided on a compassionate use basis. Clinical characteristics and outcome of patients treated with remdesivir were collected retrospectively and compared with those of patients hospitalized in the same time period. Results: A total of 51 patients were considered, of which 25 were treated with remdesivir. The median (IQR) age was 67 (59–75.5) years, 92% were men and symptom onset was 10 (8–12) days before admission to ICU. At baseline, there was no significant difference in demographic characteristics, comorbidities and laboratory values between patients treated and not treated with remdesivir. Median follow-up was 52 (46–57) days. Kaplan–Meier curves showed significantly lower mortality among patients who had been treated with remdesivir (56% versus 92%, P  < 0.001). Cox regression analysis showed that the Charlson Comorbidity Index was the only factor that had a significant association with higher mortality (OR 1.184; 95% CI 1.027–1.365; P  = 0.020), while the use of remdesivir was associated with better survival (OR 3.506; 95% CI 1.768–6.954; P  < 0.001). Conclusions: In this study the mortality rate of patients with COVID-19 under mechanical ventilation is confirmed to be high. The use of remdesivir was associated with a significant beneficial effect on survival.